ALS disease detection in EMG using time-frequency method - Doulah, A. B. M. Sayeed Ud; Iqbal, Md Asif; Jumana, Marzuka Ahmed (2012 International Conference on Informatics, Electronics and Vision, 2012)
EMG signal is a biomedical signal that measures electrical currents generated in muscles during its contraction representing neuromuscular activities. The shapes and firing rates of Motor Unit Action Potentials (MUAPs) in EMG signals provide an important source of information for the diagnosis of neuromuscular disorders. We proposed a method in this study to identify Amyotrophic Lateral Sclerosis (ALS) of biceps brachia muscle using time-frequency methods. In order to comprehend this aim EMG signal database was obtained from a normal control group consisted of 10 normal subjects aged 21-37 years & a group of patients with ALS consisted of 8 patients aged 35-67 years. EMG signals features were examined by Short Time Fourier Transform (STFT) method in time-frequency domain for detection of ALS.